Suppression of exercise-induced neutrophilia and lymphopenia in athletes by cystine/theanine intake: a randomized, double-blind, placebo-controlled trial - Titchenal C Alan; Kurihara Shigekazu; Murakami Shigeki; Ohtani Masaru (Taylor & Francis Group, 2010)
Abstract Background Intense exercise induces increased blood neutrophil counts and decreased lymphocyte counts, and leads to inflammation and immunosuppression. It was previously reported that cystine and theanine (CT) supplementation by long-distance runners before a training camp suppressed the changes of these blood parameters observed in un-supplemented control subjects after the camp. The purpose of the present study was to determine the effects of CT supplementation on the inflammatory response and immune state before and after intense endurance exercise in long-distance runners at a training camp. Methods Sixteen long-distance runners were allocated to one of two groups given CT supplements (700 mg cystine + 280 mg theanine daily) or placebo (8 in each group) for 7 days prior to and during a 9-day training camp. Daily run training averaged 19.9 km/day prior to the camp and 28.6 km/day during the camp. On the initial and final days of the camp, blood samples were collected before and after 15 km morning interval running workouts (1000 m × 15 times) and analyzed for neutrophil and lymphocyte counts and myoglobin. Results The relative change in exercise-induced blood neutrophil count (% of pre-exercise values) was significantly lower in the CT group than in the placebo group (163.3 ± 43.2% vs. 200.4 ± 19.6%, p = 0.044) on the initial day of camp, but not on the last day. The decline in lymphocyte count (% of pre-exercise values) was significantly less in the CT group than in the placebo group (60.2 ± 19.2% vs. 36.2 ± 12.0%, p = 0.010) on the initial day of camp, but not on the last day. In blood myoglobin, there was a trend toward lower % of pre-exercise values in the CT group (p < 0.09) on both measurement days. Conclusion CT supplementation significantly attenuated the increase in neutrophil count and the reduction in lymphocyte count induced by intense endurance exercise. These results suggest that CT supplementation may suppress the exercise-induced fluctuation of the blood immunocompetent cells and may help to reduce the alteration of the immune state.